Tabata workout handbook : achieve maximum fitness with over 100 high intensity interval training workout plans - Hall, Roger, ....- ([s.l.] : Hatherleigh Press,U.S., 2015)
Achieve new levels of fitness in just minutes a day with high intensity interval training (HIIT) workouts...tabata style! A long-time favorite of athletes looking to reach their peak and stay competitive, high intensity interval training (HIIT) burns body fat with more efficiency than any other method. By pushing your body close to its exercise limits for very brief periods, HIIT achieves real results in improving both cardiovascular and respiratory functions. Requiring less time than any other method of fitness, tabata, a form of HIIT, is now acknowledged to be the single most advantageous form of exercise for any number of fitness goals. Tabata lets you push your body to its physical limits—getting the results you want while avoiding stress-based injuries and unwanted setbacks. Requiring little to no equipment, tabata is as affordable as it is effective. The Tabata Workout Handbook lets you tailor the intensity of your workout to your starting ability. And since each movement only takes 4 minutes to complete, tabata is perfect for any schedule! The Tabata Workout Handbook includes: • Over 100 tabata routines, with endless possible variations • Weighted tabata workout drills, letting you work tabata into any strength-building program • Detailed, easy-to-understand exercise descriptions to help you master each tabata movement • Tips on how to best supplement your existing workout regimen, letting you customize your tabata experience to fit your needs • Tabata Tracker journal pages to help you keep track of your progress Whether you're looking to intensify an existing workout, increase your fitness results, or overcome your personal fitness plateau and reach new heights, The Tabata Workout Handbook shows you how!
4-minute workouts for every body
Keywords: Krachttraining